Options for diversifying agricultural systems to reduce pesticide use: Can we learn from nature?. (March 2022) - van der Werf, Wopke; Bianchi, Felix
There is increasing demand for farmers to reduce their use of anthropogenic inputs such as fertilizers and pesticides. It is often suggested that nature offers alternative ways to suppress pests, but what might these be? One prominent difference between most natural and agricultural systems is the diversity of plants and associated biota such as arthropod herbivores, predators and parasites, both above- and below-ground. It is often claimed that a move away from monocultures and towards greater field, farm and landscape diversity could be an important and obvious first step towards more natural pest control. This paper draws together strands of evidence on what a move to more diverse crop systems can and cannot bring to pest control. We conclude that diversification has great potential, but is not a silver bullet. Adopting a wider definition of IPM and including the environmental stewardship role of agriculture would enable a greater use of natural mechanisms for pest control, including a greater role for diversity, but would also require an economic mechanism to reward stewardship that serves wider societal needs while discouraging management that does not.